Study on laser cladding parameters of In625 nickel-based alloy powders - LI Yan-peng; WEN Hai-jun (Fenmo yejin jishu)
To determine the suitable process parameters of cladding the In625 nickel-based alloyed powders on the ZG06Cr13Ni4Mo stainless steel plates, a series tests for the laser cladding parameters were carried out by the response surface analysis, and the variance quantitative analysis of the test data was obtained by Response Surface module in Desigh-Expert software. The surface morphology and the cross-section microstructure of the multiple overlapping laser cladding samples were detected and qualitatively analyzed by the metallographic microscope. It is concluded that, when the powder feeding is the constant, the cladding layer is obviously response to the laser power and the scanning speed. The optimal cladding process parameters are determined as the laser power of 2000 W, the powder feeding of 84 g·min−1, and the scanning speed of 5 mm·s−1. The obtained samples operated by the optimal parameters show the cladding layer in high quality with the smooth surface and without porosity and cracks.